Stress and Anxiety among Two Groups of Engineering Students: A Study on Stress and Anxiety among Engineering Students in India (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Engineering education in India established amid the British period. It began with the principle concentrate on Civil Engineering and now extended its branches in various particular territories. The expanded braches of designing gives wide chances of work in different open and private associations with attractive bundles. This has brought about fame of designing courses over the nation. To take care of the demand for building courses, India is expanding its authorized admission for designing courses. In the most recent ten years 1997-2007 the endorsed quality developed from 1.15 lakhs to 5.51 lakhs. The quantity of female understudies enlisting for building courses has additionally demonstrated gigantic increment in a decade ago. Today, countless specialists have cleared out noteworthy effect on the world universally. To accomplish these positive results, understudies need to confront numerous issues and difficulties amid undergrad building courses. In the present paper, an endeavor has been made to consider the issues that prompt anxiety and tension among undergrad designing understudies. The significant concentrate of the paper is on exploring the anxiety and tension level among first year and last year undergrad building understudies. This paper additionally ponders sexual orientation contrasts in stress and nervousness among undergrad building understudies. The members of concentrate included 200 undergrad designing understudies examining in private building organization in Rashtrasant Tukdoji Maharaj Nagpur University, one of the regarded colleges in India. Information was gathered by utilizing 'Tension, Depression and Stress Scale (ADSS)' (Bhatnagar et.al, 2011). Information was examined by utilizing SPSS-20.